OPTIMALISASI PERAN KRING RESERSE SATUAN RESERSE KRIMINAL DALAM UPAYA PENYELIDIKAN DAN PENYIDIKAN TINDAK PIDANA CURANMOR DI WILAYAH HUKUM POLRES TEGAL KOTA GUNA TERCIPTANYA HARKAMTIBMAS - ADITYA VEDA (Indonesian Journal of Police Studies, 2022)
ABSTRACT OPTIMIZATION OF ROLE SATUAN RESERSE KRIMINAL IN IMPLEMENTING KRING RESERSE ACTIVITIES TO PREVENT THE CRIME OF CURANMOR IN THE JURISDICTION OF THE TEGAL CITY POLICE TO CREATE HARKAMTIBMAS Aditya veda, 18.041, Adtyavda@yahoo.co.id The National Police is a state institution whose function is to maintain internal security. With the many phenomena in society, coupled with the COVID-19 pandemic, which adds to the number of public order disturbances that occur, including gambling problems. To overcome this, there needs to be a preemptive effort from the Police, namely through Satuan Reserse Kriminal with various kinds of activities such as Kring Reserse. In this final project, the problem includes how the role of Satuan Reserse Kriminal Tegal city Police through Kring Reserse to prevent vehicle theft in the context of Harkamtibmas and what are the efforts of Satuan Reserse Kriminal Tegal city Police through Kring Reserse to prevent vehicle theft in the context of Harkamtibmas. As an analytical knife, the author uses management theory,performance theory and the concepts of Satuan Reserse Kriminal, Kring Reserse, Kamtibmas, and vehicle theft. This thesis uses a qualitative approach. The type of research is field research, while the data collection technique is through interviews, observations, and document studies. For the data analysis technique, the writer uses data reduction, data presentation, and drawing conclusions. Keywords: Role, Satuan Reserse Kriminal, Kring Reserse, Curanmor.